MODEL INTEGRATIF INTERVENSI KONSELING KESEHATAN MENTAL SISWA : KARAKTERISTIK, KOMPONEN, DAN FAKTOR YANG MEMPENGARUHINYA: SYSTEMATIC LITERATURE REVIEW - Nurul Jannati Salsabila; Defriyanto (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
This research aims to identify and synthesize the characteristics, main components, and factors that influence the effectiveness of counseling interventions in improving students' mental health. The research uses a Systematic Literature Review (SLR) approach referring to the PRISMA flow to select relevant articles. A total of 21 scientific articles that met the inclusion criteria were systematically analyzed using data extraction and thematic analysis techniques. The research results show that effective counseling interventions have the main characteristics of a holistic approach, based on initial assessment, and supported by adequate counselor competence. In addition, interventions are also flexible in form and media, including the use of technology and culture-based approaches. Factors that influence the effectiveness of interventions include individual factors (self-compassion, coping, traumatic experiences), academic factors (learning involvement), socio-cultural factors (social support and stigma), and system factors (service access and monitoring). Overall, the research findings confirm that counseling interventions must be designed in an integrative and contextual manner to achieve optimal results. This research contributes to the development of more comprehensive and evidence-based counseling intervention models in educational contexts.